The change in eigenvalue multiplicity associated with perturbation of a diagonal entry of the matrix - Johnson, Charles R. (2009)
Here we investigate the relation between perturbing the i-th diagonal entry of A 2 Mn(F) and extracting the principal submatrix A(i) from A with respect to the possible changes in multiplicity of a given eigenvalue. A complete description is given and used to both generalize and improve prior work about Hermitian matrices whose graph is a given tree.